Case Report: Severe Listeria Encephalitis With Complicated or Secondary Autoimmune Encephalitis and CNS Demyelinating Diseases - Zhang, Xiaomin; Feng, Peng; Meng, Pengfei; Li, Dongfang; Gao, Huizhong; Zhao, Yang; Yuan, Jingjing; Wang, Yongqing; Xia, Han (Frontiers in Public Health, 2022)
Background Listeria monocytogenes is an important food-borne bacterium. It rarely infects patients with complete immunity and causes meningocephalitis. Patients with severe Listeria encephalitis always experience a bad prognosis. Case Presentation A 39-year-old male patient was admitted to our hospital due to fever for more than 10 days and disturbance of consciousness accompanied by convulsions for 2 days. Metagenomic next-generation sequencing (mNGS) results showed L. monocytogenes in both cerebrospinal fluid (CSF) and blood, indicating L. monocytogenes encephalitis. Autoimmune encephalitis and central nervous system (CNS) demyelinating autoantibodies in the CSF also showed positive results. The case was finally diagnosed as severe Listeria encephalitis with complicated or secondary autoimmune encephalitis and CNS demyelinating diseases. Conclusions It is necessary to carry out infection and immunity screening in patients with severe encephalitis, especially for immunocompromised patients. mNGS plays a pivotal role in screening patients with severe and difficult neurological diseases.